Health-Related Stigma in Young Adults With Sickle Cell Disease - Jenerette, Coretta M. (2010)
Health-related stigma is increasingly becoming a major public health issue that is receiving more attention. Young adults with sickle cell disease (SCD) are at risk for health-related stigmatization due to the many challenges of the disease. SCD includes the lifelong challenges of managing the chronic illness while accessing and navigating the health care system. The burdens of the disease can affect all aspects of the lives of individuals with SCD to include physiological, psychological, and social well-being. Although others may be involved in the process of stigmatization, the purpose of this paper was to support the need to develop patient-oriented interventions to prevent and treat health-related stigma in young adults with SCD, as these individuals may face health-related stigma throughout their lives, but especially immediately after transitioning from pediatric to adult care. Additionally, the Revised Theory of Self-Care Management for Sickle Cell Disease is offered as a framework from which theory-based interventions can be derived.